1987
DOI: 10.1038/ki.1987.222
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium level and arterial calcification in end-stage renal disease

Abstract: In this paper we examine the relationship of serum levels of Ca, P, Ca X P, P/Mg, Ca X P/Mg, alkaline phosphatase, and iPTH to the development or regression of peripheral arterial calcifications (AC) in 44 patients with end-stage renal disease being treated by continuous ambulatory peritoneal dialysis (CAPD). The average follow-up time of this longitudinal study was 27 months (range 6-67 months). The patients were divided into two groups: Group A, those showing one or more increases of AC; and Group B, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 45 publications
2
122
0
Order By: Relevance
“…Vascular calcification (VC), especially in the arterial media, is probably a major contributor to arteriosclerosis in CKD (127)(128)(129)(130). Numerous autopsy and radiologic studies in the past several decades have demonstrated high rates of calcification of peripheral and central arteries (131)(132)(133)(134)(135)(136)(137)(138)(139)(140), and coronary artery calcification is even common and progressive in young adult hemodialysis patients (141). VC is probably primarily due to abnormal mineral metabolism that is seen in renal failure (141)(142)(143)(144)(145), perhaps through a complex process involving osseous metaplasia of the vascular wall components (118,119,146).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…Vascular calcification (VC), especially in the arterial media, is probably a major contributor to arteriosclerosis in CKD (127)(128)(129)(130). Numerous autopsy and radiologic studies in the past several decades have demonstrated high rates of calcification of peripheral and central arteries (131)(132)(133)(134)(135)(136)(137)(138)(139)(140), and coronary artery calcification is even common and progressive in young adult hemodialysis patients (141). VC is probably primarily due to abnormal mineral metabolism that is seen in renal failure (141)(142)(143)(144)(145), perhaps through a complex process involving osseous metaplasia of the vascular wall components (118,119,146).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…Decreased magnesium is associated with impaired endothelial function, vasospasm and atherogenesis [49] . In hemodialysis and peritoneal dialysis patients, lower serum magnesium but still within the normal range was associated with an increased severity of vascular calcification [50,51] . In vitro studies have demonstrated the protective effect of increasing magnesium concentration on vascular smooth muscle cell calcification through an upregulation of anti-calcification proteins including matrix gla protein and osteopontin [52][53][54] .…”
Section: Magnesium and Combined Magnesium-calcium Phosphate Bindermentioning
confidence: 99%
“…It has been suggested that two types of MCS may exist, with clinical and histological differences: the first is a benign, slowly progressive, and essentially asymptomatic form with thin medial calcifications and little or no narrowing of the arterial lumen; the second is a malignant, rapidly progressive form in which massive and extensive medial calcifications may displace the internal elastic lamina toward the lumen causing luminal narrowing [5].…”
mentioning
confidence: 99%